2013
DOI: 10.1016/j.jimonfin.2013.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The consumption-real exchange rate anomaly with extensive margins

Abstract: This paper investigates a consumption-real exchange rate anomaly from the open macroeconomics literature known as the Backus-Smith puzzle . We both analytically and quantitatively examine how an expansion of trade along extensive margins can contribute to the puzzle's resolution. Our argument is based on 1) a wealth e¤ect due to changes in the number of product varieties, 2) statistical ine¢ ciency in measuring the number of product varieties, and 3) market incompleteness. Contrary to complete asset markets wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Bahmani-Oskooee & Xi (2012) include the volatility of the exchange rate as another determinant of consumption in the consumption function. Employing the data from Japan, Canada, and the US, they found that the VEX (Note 2) hurts domestic consumption in case of Canada, while it demonstrates positive impact in case of US and Japan, supporting the argument of Obstfeld & Rogoff 1998. Only few empirical studies are present in the ample body of the literature on the relationship between the volatile exchange rate and the domestic consumption such as Bahmani-Oskooee and Xi (2011), Bahmani-Oskooee & Xi, (2012), Bahmani-Oskooee & Hajilee, (2012), Hamano, (2013), Bahmani-Oskooee, Kutan, & Xi, (2015). A critical review of the entire body of the concentrated literature brought off on the nexus between VEX and the domestic consumption, divulge that researchers have analysed the relationship regarding only a few economies, considering time-series data.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Bahmani-Oskooee & Xi (2012) include the volatility of the exchange rate as another determinant of consumption in the consumption function. Employing the data from Japan, Canada, and the US, they found that the VEX (Note 2) hurts domestic consumption in case of Canada, while it demonstrates positive impact in case of US and Japan, supporting the argument of Obstfeld & Rogoff 1998. Only few empirical studies are present in the ample body of the literature on the relationship between the volatile exchange rate and the domestic consumption such as Bahmani-Oskooee and Xi (2011), Bahmani-Oskooee & Xi, (2012), Bahmani-Oskooee & Hajilee, (2012), Hamano, (2013), Bahmani-Oskooee, Kutan, & Xi, (2015). A critical review of the entire body of the concentrated literature brought off on the nexus between VEX and the domestic consumption, divulge that researchers have analysed the relationship regarding only a few economies, considering time-series data.…”
Section: Introductionmentioning
confidence: 80%
“…It is only the consumption, which gives the primary thrust to production (Campbell & Mankiw, 1989;Saha & Zhang, 2013).Moreover, the role of household aggregate consumption in the process of a country's economic growth is vital since it defines the standard of living of inhabitants, while the living standard defines the economic status of a country (Murase, 2013). Therefore, it is imperative for economists and the policymakers to understand and to identify the determinants of consumption which can encourage and curtail the economics activities during the recessionary and inflationary times respectively (Hamano, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without fixed export costs, we have four fewer variables and four fewer equations. The supply side of the model collapses to the one similar to Hamano (2013).…”
Section: The Model Without Fixed Export Costsmentioning
confidence: 96%
“…This pattern, known as the Backus-Smith Puzzle, is even more surprising given the rise in international capital flows and the progressive integration of world financial markets. Masashige Hamano 42 presents a possible resolution of the puzzle based on three elements: (i) a wealth effect due to changes in the number of product varieties; (ii) statistical inefficiency in measuring the number of product varieties; and (iii) market incompleteness.…”
Section: Fixed Vs Flexible Exchange Ratesmentioning
confidence: 99%